WO3 Nanowires on Graphene Sheets as Negative Electrode for Supercapacitors. (20th February 2017) - Liu, Bo; Wang, Yan; Jiang, Hong-Wu; Zou, Ben-Xue
Abstract : WO3 nanowires directly grown on graphene sheets have been fabricated by using a seed-mediated hydrothermal method. The morphologies and electrochemical performance of WO3 films prepared by different process were studied. The results show that the precoated nanoseeds and graphene sheets on graphite electrode provide more reactive centers for the nucleation and formation of uniform WO3 nanowires. The WO3 nanowires electrode exhibits a high area specific capacitance of 800 mF cm −2 over negative potential range from −1.0 V to 0 V versus SCE in 1 M Li2 SO4 solution. A high performance electrochemical supercapacitor assembled with WO3 nanowires as negative electrode and PANI/MnO2 as positive electrodes over voltage range of 1.6 V displays a high volumetric capacitance of 2.5 F cm −3, which indicate great potential applications of WO3 nanowires on graphene sheets as negative electrode for energy storage devices.